1994
DOI: 10.1046/j.1525-1438.1994.04010061.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian transposition in young patients with invasive cervical cancer receiving radiation therapy

Abstract: Twenty-two patients with invasive cervical cancer had ovarian transposition. Fifteen patients received whole pelvic external radiation therapy via a teletherapy unit, and nine patients also received one or two intracavitary insertions. Ovarian function was measured by serum gonadotropins, FSH, and LH. We were unable to measure gonadotropin levels in four patients because they were lost to follow-up after completion of radiation therapy. Five patients developed postmenopausal symptoms; in two the ovaries were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Ovarian transposition outside the pelvic irradiation field has been shown to reduce the ovarian irradiation dose by 90% to 95% compared with the untransposed ovary. 18,28 Laparoscopic surgery has been one of the important innovations in modern-day surgery, allowing the patient to have a fast recovery. The published laparoscopic experience with ovarian transposition has been limited to few small series.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian transposition outside the pelvic irradiation field has been shown to reduce the ovarian irradiation dose by 90% to 95% compared with the untransposed ovary. 18,28 Laparoscopic surgery has been one of the important innovations in modern-day surgery, allowing the patient to have a fast recovery. The published laparoscopic experience with ovarian transposition has been limited to few small series.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian failure can occur after single dose of 400 cGy or a fractionated regimen of 1,500 cGy during 10 days. The radiation dose inducing ovarian failure after treatment decreases with increasing age (6). A study reported that ovarian function was preserved in 64% of patients with bilateral ovarian transposition who received a radiation dose of <500 cGy (7).…”
Section: Discussionmentioning
confidence: 99%
“…Haie-Meder et al [3] have reported that almost 85% of women undergoing radiotherapy for a wide variety of pelvic malignancies following lateral ovarian transposition will continue to demonstrate gonadal function for ovarian doses of less than 5 Gy. Other studies have suggested that an ovarian dose lower than 5 Gy is required to induce ovarian damage [10,12,14,19]. Ash [19] has reported that a fractionated dose to ovaries of 4 Gy may cause a 30% incidence of sterility in women aged 15 Á40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Chambers et al [10] and Van Eijkeren et al [14] found a steep dose response effect at 3 Gy for induction of early menopause in women undergoing radiotherapy for cervical cancer after lateral ovarian transposition. Husseinzadeh et al [12] reported that the radiation dose to transposed ovaries should be limited to 3 Gy for ovarian function preservation in young patients irradiated for invasive cervical cancer. To be conservative, a radiation dose of 3 Gy was considered as the threshold value for ovarian damage in this study.…”
Section: Discussionmentioning
confidence: 99%